Territorial peculiarities of development of tourism in the Republic of Kazakhstan - Saduov, A.Zh.; Mukanov, B.O.; Nursultan, D.T. (BUKETOV BUSINESS REVIEW, 2019)
The Republic of Kazakhstan is characterized by uneven development of the territory for tourist and recreational purposes. In the article areas with high ratings of predisposition for the development of summer tourism are discussed. The main areas of Kazakhstan, favorable for the development of winter types of tourism are considered. The regions of Kazakhstan are quite different in the composition of natural resources used in the organization of recreation and tourism, in their size and combination, as well as in natural and economic factors that facilitate or impede their development. In this regard, the prospects for the territorial development of the tourist market of the Republic of Kazakhstan are considered. The development of inbound and domestic tourism in Kazakhstan will depend on a number of market trends — in tourism in general, the economy, demography, ecology, technology and other areas. The article proposed the direction of development of tourism in the Republic of Kazakhstan in certain tourist clusters with a competitive tourist business, in which tourism professionals who offer attractive tourist products in the domestic and international tourism markets should develop tourism. The development in this direction should contribute to a powerful and stable growth of income from tourism activities for all involved stakeholders — the state, business and employees.